2005
DOI: 10.1002/gps.1315
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptom quality and neuropsychological performance in dementia

Abstract: The division of depressive symptoms in factors of mood and motivation disturbance contributes to insight into the relationship between depression and cognitive dysfunction in dementia. An advantage of the motivation disturbance factor compared to the regular apathy scales is that it consists of depressive symptoms. Therefore, it becomes evident that apathy or impaired motivation may occur in patients with dementia both in and outside the context of a depressive syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
7
6
0
Order By: Relevance
“…In these, the motivation symptoms contributed for as much as 68% to the total number of depressive symptoms. This is the same finding as we had in another group of demented subjects, although in that case, the level of dementia as well as that of depression was considerably less severe than in the present study (Janzing et al, 2005). No significant relationships were observed between the mood symptoms and scores on neuropsychological tests and also consistent with earlier studies there was no significant correlation between a general measure of depression and specific neuropsychological tests performance (Kuzis et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In these, the motivation symptoms contributed for as much as 68% to the total number of depressive symptoms. This is the same finding as we had in another group of demented subjects, although in that case, the level of dementia as well as that of depression was considerably less severe than in the present study (Janzing et al, 2005). No significant relationships were observed between the mood symptoms and scores on neuropsychological tests and also consistent with earlier studies there was no significant correlation between a general measure of depression and specific neuropsychological tests performance (Kuzis et al, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the group was thoroughly selected and revealed a rather large cohort of clearly defined clinical subjects. This is the second study in which we have confirmed a relationship between low scores on the VFT and the motivational dimension of depression (Janzing et al, 2005). In contrast to our former study, there was no association between the MMSE total score and both the total number of depressive symptoms and the number of motivational symptoms.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…This could be explained with the heavy intellectual and personality decline in severe dementia, which makes nearly impossible the formation and verbalization of psychotic and non-psychotic symptoms. Janzing et al (2005) described depressive syndromes in patients with mild dementia and proposed that sharing of depressive symptoms reflects relatively intact cognitive functions (18). In our study the comparison on a syndrome level revealed that EO-AD patients were more psychotic, while LO-AD-more anxious.…”
Section: Discussionsupporting
confidence: 44%
“…For the interpretation, it is important to realize that the number of depressive symptoms is not a direct measure of the severity of depression in subjects with dementia: many of the symptoms occur outside the context of a depressive syndrome [26] and may also be symptoms of dementia [10] .…”
Section: Discussionmentioning
confidence: 99%